Effect of replacing soybean meal with dried distillers grains in meat goat diets - Ivey, Lauren T.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Market goat nutrition has received limited attention and their requirements have often been extrapolated from other species (cattle and sheep) due to a lack of information. Specifically, there is very limited data available regarding the role of feeding dried distillers grains with solubles (DDGS) to goats. With the per protein unit cost advantage of DDGS over SBM being $1.86, DDGS would clearly price into goat diets as a protein source (October 26, 2017 U.S. Grains Council Report). However, there is insufficient data to base recommendations for potential inclusion of DDGS in a diet. Our objective is to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. Forty-eight meat goat kids (approximately 70 d of age, initially 28.2kg) were used in a completely randomized design. Animals were housed at the Kansas State University Sheep and Meat Goat Center with 3 kids per pen (4 pens per treatment). Pens were allotted into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All diets were pelleted at the Kansas State University feed mill with pellets formulated to contain roughage so no supplemental forage was needed. After a 14 day step up period, diets were fed for 46 days with goats and feeders weighed weekly to determine ADG, ADFI and G:F. Two goats per pen were randomly selected and slaughtered at a USDA-inspected facility with carcass data collected. Data was analyzed using the GLIMMIX procedure of SAS, with pen as the experimental unit and 0.05 as the alpha value. Dietary treatment increased (P<0.0001) G:F but not overall ADG or ADFI (P>0.10) due to a linear improvement (P<0.02) in overall ADG and G:F with increasing DDGS. Overall, the greatest feed efficiency was observed at goats fed either 66% or 100% of SBM replaced by DDGs compared to those fed 0% or 33% of SBM replaced by DDGS. There was no evidence of effect (P>0.10) on carcass measurements. In summary, including DDGS in replacement of SBM in Boer Goat diets did not impact ADG, ADFI or carcass measurements but did improve G:F.
Keywords: Spring 2018